Managemen Pengendalian Hipertensi Dengan Pendekatan Edukatif Dan Komprehensif Dalam Mewujudkan Kemandirian Self-Care Kondisi Kronik Pada Komunitas Dusun 4 Desa Pekik Nyaring, Kabupaten Bengkulu Tengah, Propinsi Bengkulu - Ramadanti, Nopita Dwi; Wilantara, Anggi; Pebrianti, Nesa; Handayani, Tita Septi; Sari, Lezi Yovita (Universitas Dehasen Bengkulu, 2024)
This community service was carried out in Hamlet 4, Pekik Nyaring Village, Pondok Kelapa District, Central Bengkulu Regency, chosen because there was data on hypertension among adults and the elderly obtained from data from the working area of the Pekik Nyaring District Health Center. Pondok Kelapa Kab. Central Bengkulu. After interviews with the community, the problem of hypertension in Hamlet 4, Pekik Nyaring Village, was mostly caused by age, lack of concern for routine blood pressure checks because they were busy gardening, and limited health services. Facing this situation, students discussed with a team of field supervisors, the community health center, the hamlet head, cadres and residents of Hamlet 4 of Pekik Nyaring Village to determine the program that would be implemented. The stages of implementing this community service activity were carried out by interviewing the Kadun (hamlet head), cadres, and the community health center (CI) regarding the problems in Hamlet 4, Pekik Nyaring Village. Then the activity program was determined through FGD (Focus Group Discussion) which would be carried out to deal with existing problems in Hamlet 4, Pekik Nyaring Village. Student counseling will provide a pre-test questionnaire related to hypertension. Next, a question and answer session was held with the community who were given education. The final stage of this activity is that participants are given a post-test questionnaire. Implementation of direct improvements related to foot reflexology massage therapy and Mindfulness Based Stress Reduction (MBSR), increasing public knowledge about hypertension from 18% to 98% as seen from the total score of the pre and post test questionnaires. The results show that hypertension exercise can reduce the average systolic blood pressure by 10mmHg and diastolic blood pressure by 5mmHg. Post-training evaluation showed that cadres were able to instill foot reflexology techniques, including recognizing reflex points related to blood pressure, as well as conducting massage sessions that helped residents reduce muscle tension and other physical symptoms of hypertension. Live demonstrations carried out by cadres during the session demonstrated the training's ability to be able to teach and guide MBSR techniques to other communities. Overall, this community service program succeeded in achieving the main goal of increasing community awareness and skills in managing hypertension. With significant indicators of success in increasing knowledge and controlling blood pressure in the community, as well as increasing the skills of Hamlet 4 Pekik Nyaring Village cadres in carrying out foot reflexology massage therapy and MBSR therapy in dealing with stress due to hypertension.